Isolated fallopian tube torsion in an adolescent: a diagnostic challenge - Bivar, Leonor; Castro, Ana; Teixeira, Neusa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Torsion of the fallopian tube without ovarian involvement is an extremely rare event and often difficult to diagnose, but noteworthy, cause of lower abdominal pain. The authors describe a case related to a 14- year-old adolescent with acute lower abdominal pain and vomiting presented to the gynaecological emergency department. Blood tests exhibited modest biochemical parameters of inflammation and a transvaginal ultrasound showed a left adnexal tubular cystic mass with normal ovarian appearance. A diagnostic laparoscopy revealed an isolated fallopian tube torsion. The tube was able to be untwisted with restoration of pelvic anatomy and the follow-up was uneventful. The authors describe a challenging diagnosis in an adolescent in which delayed intervention could compromise her reproductive future. Tubal torsion should however be kept in mind in the differential diagnosis of lower abdominal pain in women of all ages.